O rádio nas redes sociais: uma análise dos conteúdos da UFT FM no Instagram - Lima, Victória Milhomem (Universidade Federal do Tocantins, 2020)
With the popularization of social networks on the Internet, traditional communication vehicles began to use these digital platforms as channels of communication with society, in addition to migrating and adapting their programming to reach new audiences. Based on this reflection, the present work carried out an analysis of the publications of the educational radio UFT FM in Instagram, with the objective of identifying what the contents of the station are and how they are approached in the period of two years. The methodological procedures adopted were the bibliographic research, the principles of Content Analysis and the qualitative approache. The results of the study lead us to the conclusion that both the contents and the approach of the publications need more planning, organization and strategies, so that they can have a greater potential in this social network, as well as satisfactorily meet the objectives that the broadcaster proposes in its guidelines.